2019
DOI: 10.1111/cch.12642
|View full text |Cite
|
Sign up to set email alerts
|

Depression among Chinese Left‐Behind Children: A systematic review and meta‐analysis

Abstract: Background: In China, there are approximately 70 million children, nearly 25% of the child population, who are left behind in the care of other family members when their parents migrate to urban areas, for increased economic opportunities. This paper presents a systematic review and a meta-analysis of studies that have examined the phenomenon of depression among these left-behind children (LBC). Methods: Six hundred three papers published between 2000 and 2017 were retrieved from five databases (China National… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 34 publications
0
34
1
Order By: Relevance
“…Specifically, the association between perceived social support and loneliness was stronger for left-behind students in comparison to non-left-behind students. This might be attributed to the absence of parental care among left-behind students, including physical companionship, parental supervision and parental guidance ( 57 ), which might contribute to the strengthened association between perceived social support and loneliness among left-behind adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, the association between perceived social support and loneliness was stronger for left-behind students in comparison to non-left-behind students. This might be attributed to the absence of parental care among left-behind students, including physical companionship, parental supervision and parental guidance ( 57 ), which might contribute to the strengthened association between perceived social support and loneliness among left-behind adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Although studies have shown that working in the developed area can increase family income and raise family status in the local area, it is rarely beneficial for leftbehind children [2]. Researches show that left-behind children have more mental health problems than nonleft-behind children [3][4][5][6], including a higher risk of depression [7], and anxiety [8], a stronger sense of loneliness [9], and higher suicide risk [10], highlighting severe psychological problems of these children and tough challenges posed by the problems. Depression is the most common mental health problemin childhood [11], and depression in children and adolescents is usually the first episode of depression [12].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, these affected children are forced to live without their parents and receive less parental care and education (Tang et al, 2019;Wu et al, 2019). Studies have shown that parental migration has a negative effect on children's mental health, resulting in low self-esteem, loneliness, anxiety, depression and even a high prevalence of suicidal ideation (Ai & Hu, 2014;Ding et al, 2019;Tang et al, 2018;Xiao et al, 2019). In fact, compared with non-left-behind children (NLBC), LBC are more likely to develop emotional or behavior problems and have significantly more emotional symptoms, more psychopathological behaviors and fewer pro-social behaviors (Fan et al, 2010;Wang et al, 2019).…”
Section: Introductionmentioning
confidence: 99%